Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Farm level natural capital accounting to connect on-ground agroforestry decision making with local and global imperatives: A case study in Tasmania, Australia - Daniel S. Mendham; Anthony O'Grady; Stephen Stewart; Jacqueline R. England; Suzanne M. Prober; Thomas Baker; Shaun Brooks; Martin Moroni; Chris Ware; Aysha Fleming; Stephen Roxburgh; Sue Ogilvy; et al. (Agricultural Systems, 2026)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Anti-drug Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Kelli Phillips; Charles Scott Hottenstein; Paul Chamberlain; Viswanath Devanaryan; Carol Gleason; Joanne Goodman; Marta Starcevic Manning; Shobha Purushothama; Susan Richards; Honglue Shen; et al. (The AAPS Journal, 2022)
Evolving immunogenicity assay performance expectations and a lack of harmonized anti-drug antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. Following debate at the American Association of Pharmaceutical Sciences National Biotechnology Conference, a group was formed to address these gaps. Over the last 3 years, 44 members from 29 organizations (including 5 members from Europe and 10 members from FDA) discussed gaps in understanding immunogenicity assay requirements and have developed harmonization tools for use by industry scientists to facilitate filings to health authorities. Herein, this team provides testing and reporting strategies and tools for the following assessments: (1) pre-study validation cut point; (2) in-study cut points, including procedures for applying cut points to mixed populations; (3) system suitability control criteria for in-study plate acceptance; (4) assay sensitivity, including the selection of an appropriate low positive control; (5) specificity, including drug and target tolerance; (6) sample stability that reflects sample storage and handling conditions; (7) assay selectivity to matrix components, including hemolytic, lipemic, and disease state matrices; (8) domain specificity for multi-domain therapeutics; (9) and minimum required dilution and extraction-based sample processing for titer reporting. Graphical Abstract

Effective coastal adaptation needs accurate hazard assessment: a case study in Port Resolution, Tanna Island Vanuatu - Gaelle Faivre; Rodger Tomlinson; Daniel Ware; Saeed Shaeri; Wade Hadwen; Andrew Buckwell; Brendan Mackey (Climatic Change, 2022)
Developing countries face risks from coastal hazards that are being amplified by climate change. The selection of effective adaptation interventions to manage these risks requires a sufficiently accurate assessment of the coastal hazard at a given location. Yet challenges remain in terms of understanding local coastal risks given the coarseness of global wave models and the paucity of locally scaled data in most developing countries, including Small Island Developing States (SIDS) like Vanuatu. This paper aims to examine the differences in hazard assessment and adaptation option selections arising from analyses using globally versus locally scaled data on coastal processes. As a case study, we focused on an eroding cliff face in Port Resolution on Tanna Island, Vanuatu, which is of concern to the local community and government authorities. The coastal process modeling revealed that the global wave data generated unrealistically high predictions of wave height within Port Resolution Bay. Expensive engineering adaptations designed to provide coastal protection were therefore likely to fail in preventing ongoing cliff erosion. In this case, the best adaptation solution involves changing land use to revegetate and help stabilize the cliff top. Our case study highlights the importance of accurate hazard assessment, especially in data-poor regions where the extrapolation of global datasets and models in the absence of local data can result in poor adaptation decision-making. Furthermore, the multidisciplinary approach applied here can be applied in other data-poor regions to strengthen analyses exploring the benefits of local adaptation interventions.

Using Historical Responses to Shoreline Change on Australia’s Gold Coast to Estimate Costs of Coastal Adaptation to Sea Level Rise - Daniel Ware; Andrew Buckwell; Rodger Tomlinson; Kerrie Foxwell-Norton; Neil Lazarow (Journal of Marine Science and Engineering, 2020)
Climate change impacts, sea level rise, and changes to the frequency and intensity of storms, in particular, are projected to increase the coastal land and assets exposed to coastal erosion. The selection of appropriate adaptation strategies requires an understanding of the costs and how such costs will vary by the magnitude and timing of climate change impacts. By drawing comparisons between past events and climate change projections, it is possible to use experience of the way societies have responded to changes to coastal erosion to inform the costs and selection of adaptation strategies at the coastal settlement scale. The experience of implementing a coastal protection strategy for the Gold Coast’s southern beaches between 1964 and 1999 is compiled into a database of the timing, units, and cost of coastal protection works. Records of the change to shoreline position and characteristics of local beaches are analysed through the Bruun model to determine the implied sea level rise at the time each of the projects was completed. Finally, an economic model updates the project costs for the point in the future based on the projected timing of sea level rise and calculates a net present value (NPV) for implementing a protection strategy, per km, of sandy beach shoreline against each of the four representative concentration pathways (RCP) of the Intergovernmental Panel on Climate Change (IPCC) to 2100. A key finding of our study is the significant step-up in expected costs of implementing coastal protection between RCP 2.6 and RCP 8.5—from $573,792/km to $1.7 million/km, or a factor of nearly 3, using a social discount rate of 3%. This step-up is by a factor of more than 6 at a social discount rate of 1%. This step-up in projected costs should be of particular interest to agencies responsible for funding and building coastal defences.

The real-time needs of emergency managers for tropical cyclone storm tide forecasting: results of a participatory stakeholder engagement process - Joanna Burston; Daniel Ware; Rodger Tomlinson (Natural Hazards, 2015)